Analysis of Merchandising System in Metro Cash and Carry LLC - Tatiana G. TRUBCHENKO; Ekaterina V. MENSHIKOVA; Nina V. POTEKHINA; Anatolii N. DREVAL; Zoya V. KRINITCYNA; Oleg V. KHAZANOV; Nataliya V. SHAFTELSKAYA; Marina V. VERKOVSKAYA (Communications of International Proceedings, 2021)
In the intense competition for consumers, national and foreign retail chains are developing new trade formats and improving the trade service system. One of the elements of increasing a store's competitiveness is the use of a merchandising system. While the issues of using merchandising in retail chains are well studied, the use of its tools in cash-and-carry stores remains underdeveloped. The specific nature of such stores is that they combine the features of a hypermarket, a warehouse store and a logistics center. The article examines the system of merchandising in Metro LLC (Tomsk) and provides recommendations for its optimization. Thus, the use of the store space, the layout and the advertising (POS) materials inside the sales area is analysed, as well as the direction of consumer traffic flow, taking into account the Golden Triangle rule, where the vertices connect the following zones: entrance – the best-selling product – checkout. Despite the fact that Metro LLC is a trading subdivision of METRO Group based in Germany with many stores worldwide, and it has been operating in the cash-and-carry format in Tomsk since 2010 with an established customer base and a distinctive marketing system, many merchandising aspects still have some drawbacks and require optimization.
Keywords: Retail Network; Cash-And-Carry Format; Merchandising; POS Materials; Product Display